(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The article is devoted to the study of word prosody in Turkic languages. At the heart of all Turkic languages, including the Kazakh language, the basis of vocabulary is a syllable (one-syllable word). It always has a meaning and is the root of the word. It is in it that the type of synharmonism is contained, which is universally ("legislative") transmitted to all suffixes and inflections that join it. Each synharmophoneme of the Kazakh language in the composition of a word is combined with synharmophonemes of one synharmotimbre (solid synharmophone with soft synharmophone, soft synharmophone with soft synharmophone). In Kazakh and other Turkic languages, synharmonism universally embraces the entire word, no matter how polysyllabic it may be. Synharmonism is also the basis of Turkic word formation and word formation